Immunobullous disorders: Clinical histopathological and immunofluorescence study of thirty-six cases - Srinath M Kambil; P Madavamurthy (Wolters Kluwer Medknow Publications, 2014)
Background: Immunobullous disorders are characterized by antibody-mediated bullous lesions affecting the skin and mucosa. Accurate diagnosis of these disorders requires clinicopathological correlation along with immunofluorescence study. Aims and Objectives: To study the clinical, histopathological, and immunopathological features of immunobullous disorders and to analyse the utility of immunofluorescence in the diagnosis of these disorders. Materials and Methods: A total of 36 cases of immunobullous disorders observed over a span of 2 years in our institution were studied. Detailed clinical examination, histopathological examination and immunofluorescence study were done in all cases. Results: Out of 36 cases studied, 18 cases (50%) belonged to pemphigus group, 10 cases (27.78%) were bullous pemphigoid (BP), 5 cases (13.89%) were linear IgA disease (LAD), 2 cases (5.56%) were cicatricial pemphigoid (CP) and 1 case (2.77%) was lichen planus pemphigoides (LPP). Twenty-one patients (58.33%) were in the age group of 21-60 years, 9 patients (25%) were above 60 years and 6 patients (16.67%) were below 20 years. Histopathology of all cases of pemphigus vulgaris (PV) showed suprabasal bulla with acantholytic cells. Pemphigus foliaceus (PF) showed subcorneal bulla in all three cases. Immunofluorescence in all 15 cases of PV showed IgG deposition in intercellular substance (ICS) and C3 deposition in ICS in six cases. PF showed IgG deposition in ICS in all three cases. BP and CP showed deposition of IgG and C3 in a linear band at basement membrane zone (BMZ) in all cases. All cases of LAD showed linear IgA band at BMZ. Conclusion: In three cases (two cases of BP and 1 LAD), immunofluorescence was absolutely essential to come to a final diagnosis, while in two cases of CP immunofluorescence helped in confirming the clinical diagnosis as histopathological finding was nonspecific. In the remaining cases it helped in confirming the diagnosis suggested by clinical examination and light microscopy.